2018
DOI: 10.1007/s00773-018-0530-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of a fan-shaped Mewis duct before a propeller on propulsion performance

Abstract: To define the guidelines for the design of a Mewis duct for a small bulk cargo ship, a numerical study was carried out to investigate the effects of a fan-shaped Mewis duct on propeller performance of a 38,000 t bulk cargo ship with a three-blade propeller. Calculations were performed using the STAR-CCM+ software based on the solution of the Reynolds averaged Navier-Stokes (RANS) equation. Computations were carried out for a wide range of locations from 0.11D to 0.21D upstream from the propeller disc, a radius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…𝜀 and k are found by semi-experimental Eqs. ( 10) and (11). In the following relation, 𝜎 𝜀 is the turbulent Schmidt number and equal to 1.3, 𝜎 𝑘 is the Prandtl number and equal to 1, G (shear production term) is the turbulence kinetic energy produced by the average flow-turbulent flow field interaction and B is the production-buoyancy loss due to the flow fluctuating density field.…”
Section: Standard K-𝜺 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…𝜀 and k are found by semi-experimental Eqs. ( 10) and (11). In the following relation, 𝜎 𝜀 is the turbulent Schmidt number and equal to 1.3, 𝜎 𝑘 is the Prandtl number and equal to 1, G (shear production term) is the turbulence kinetic energy produced by the average flow-turbulent flow field interaction and B is the production-buoyancy loss due to the flow fluctuating density field.…”
Section: Standard K-𝜺 Modelmentioning
confidence: 99%
“…Many numerical and experimental works were carried out to analyze and design the ESD [6][7][8][9][10][11]. Using the vortex lattice method (VLM) and defining a propeller blade surface replaced by the vortex distribution.…”
Section: Introductionmentioning
confidence: 99%
“…As the interaction between the water jet propeller system and the hull differs significantly from a traditional, separate water jet propeller system, CFD technology can be useful in simulating and predicting the model prior to experimentation. Chang et al (2018) utilized Reynolds average stress method (RANS) solution to explore the effect of energy-saving ducts on propeller performance in hulls with sector-shaped ducts installed in front of the propeller. Their findings revealed that the presence of the energy-saving ducts enhanced the propeller efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Often, indeed, improvements observed at the model scale were not completely confirmed in full-scale, suggesting the need to account for Reynolds effects in the very preliminary phase of the process to exploit possible additional savings. Systematic analyses of several ESD concepts [25] have evidenced the strict connection of the hull shape (and relative flowfield) to the ESD geometry and its capability to provide positive effects on the propulsion system. Self-propulsion modeling, in a similar way in this context, appeared as the most appropriate framework for the evaluation (and the exploitation, during the design process) of the ESD-propeller-hull interactions and to account for the most suitable "key performance indicators" driving the design of the device.…”
Section: Introductionmentioning
confidence: 99%